Multivariable analysis for predicting lower limb muscular strength with a hip-joint exoskeleton - Kang, Byungmun; Lee, Changmin; Kim, Dongwoo; Lee, Hwang-Jae; Lee, Dokwan; Jeon, Hyung Gyu; Kim, Yoonmyung; Kim, DaeEun (Frontiers in Bioengineering and Biotechnology, 2024)
We propose a novel approach to measuring muscular strength in young, healthy individuals using Bot Fit, a hip-joint exoskeleton, during resistance exercises. In this study, we introduced performance metrics to evaluate exercise performance during both short and extended durations of three resistance exercises: squats, knee-ups, and reverse lunges. These metrics, derived from the robot’s motor signals and sEMG data, include initial exercise speed, the number of repetitions, and muscle engagement. We compared these metrics against baseline muscular strength, measured using standard fitness equipment such as one-repetition maximum (1RM) and isometric contraction tests, conducted with 30 participants aged 23 to 30 years. Our results revealed that initial exercise speed and the number of repetitions were significant predictors of baseline muscular strength. Using statistical multivariable analysis, we developed a highly accurate model (R = 0.884, adj. R2 = 0.753, p-value < 0.001) and an efficient model (with all models achieving R > 0.87) with strong explanatory power. This model, focusing on a single exercise (squat) and a key performance metric (initial speed), accurately represents the muscular strength of Bot Fit users across all three exercises. This study expands the application of hip-joint exoskeleton robots, enabling efficient estimation of lower limb muscle strength through resistance exercises with Bot Fit.